Robust fault detection of singular LPV systems with multiple time-varying delays - Hassanabadi, Amir Hossein; Shafiee, Masoud; Puig, Vicenç (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the robust fault detection problem for LPV singular delayed systems in the presence of disturbances and actuator faults is considered. For both disturbance decoupling and actuator fault detection, an unknown input observer (UIO) is proposed. The aim is to compute a residual signal which has minimum sensitivity to disturbances while having maximum sensitivity to faults.
Keywords: singular delayed LPV systems; fault detection; unknown input observer (UIO); robustness; fault sensitivity